Asthma symptoms improvement in moderate persistent asthma patients with gastroesophageal reflux disease (GERD): the role of proton-pump inhibitor (Medical Journal of Indonesia, 2008)
This study aimed to evaluate effect of proton pump inhibitor (esomeprazole) on asthma symptoms, use of inhaled bronchodilator and peak expiratory flow rate (PEFR) in moderate persistent asthma with gastroesofageal refluks disease (GERD). This randomized single blind, controlled clinical trial study was conducted at Persahabatan Hospital, Jakarta from July 2004 until October 2005. Samples were moderate persistent asthma patients with GERD. GERD is diagnosed GERD symptoms and proof of oesophagitis from endoscopy and or histapatologic examination from oesophagus biopsy. Phase 1:2 week run-in period patient received inhaled budesonide 2x200 ug/day. Phase 2: patient randomised to receive inhaled budesonide 2 x 400 ug/day with esomeprazole 40 mg/day or without esomeprazole (control group) for 8 weeks. Phase 3: 4 week wash out period, patient receive inhaled budesonide 2 x 200 ug/day. Diary cards were assessed at run-in periode, after treatment 4 weeks, 8 weeks and wash out. There were 32 patients (23 female and 9 male) completed the study. Mean total asthma symptoms score daily were significantly decreased on esomeprazole vs without esomeprazole after 8 weeks (-2.29 vs -0.90; p < 0.05). Mean use of inhaled bronchodilator was significantly decreased on esomeprazole vs without esomeprazole after 8 weeks (-1.09 vs -0.42; p < 0.05). Morning and evening PEFR improved higher on esomeprazole than without esomeprazol but were not significantly difference. In conclusion, administration esomeprazole 40 mg daily improved asthma symptoms and lower the use of inhaled bronchodilator in moderate persistent asthma patients with GERD. (Med J Indones 2008; 17: 169-74)